KARSINOMA ADENOSKUAMOSA ENDOMETRIUM - Loho, Lily (UNIVERSITAS SAM RATULANGI, 2009)
Abstrak: Karsinoma endometrium (KE) sering mengandung fokus-fokus metaplasia skuamosa. Bila komponen skuamosa jinak disebut adenoakantoma, yang prognosisnya tidak berbeda bermakna dengan bentuk murni adenokarsinoma. Bila komponen tersebut ganas disebut karsinoma adenoskuamosa, dengan pertumbuhan yang lebih agresif. Di Amerika Serikat insiden KE adenoskuamosa masih tinggi, sedangkan di Laboratorium Patologi Fakultas Kedokteran Universitas Sam Ratulangi Manado jenis ini sangat jarang ditemukan. Kami melaporkan sebuah kasus KE adenoskuamosa seorang perempuan berusia 53 tahun yang telah dilakukan histerektomi radikal dengan diagnosis klinis mioma uteri dan diagnosis patologik karsinoma sel skuamosa tanpa keratinisasi dari hasil kerokan endometrium tiga minggu sebelumnya. Diagnosis akhir kasus ini adalah KE adenoskuamosa tipe I, derajat dua, dengan invasi ke lapisan dalam miometrium. Tidak ditemukan invasi ke jaringan lain atau metastasis ke kelenjar getah bening. Prognosis kasus ini cukup baik. Kata kunci: karsinoma endometrium, adenoskuamosa, klasifikasi. Â Â Abstract: Adenocarcinoma of the endometrium frequently contains foci of squamous metaplasia. If the squamous component is benign, it is called adenoacanthoma. On the other hand, if the squamous component is malignant, it is called adenosquamous carcinoma, which grows much more aggressively. The prognosis of adenoacanthoma does not differ significantly from that of pure adenocarcinoma. In the United States the incidence of adenosquamous carcinoma of the endometrium is still high, while in the Pathology Laboratory of the Medical Faculty, University of Sam Ratulangi, Manado this type is very rarely identified. We reported a case of adenosquamous carcinoma of the endometrium in a 53-year-old female that had undergone a radical hysterectomy due to a clinical diagnosis of uterine myoma and a pathologic diagnosis of nonkeratinizing squamous cell carcinoma for which she underwent an endometrial curettage three weeks before. After the operation, the final diagnosis of this case was adenosquamous carcinoma of the endometrium type I, grade two, with deep invasion into myometrium. There was no invasion into other tissues and no metastasis to lymph nodes. The prognosis of this case was good. Key words: endometrial carcinoma, adenosquamous, clasificassion.